The Influence of Service Quality on Perceived Value and Perceived Risk as Mediation and its Impact on Customer Satisfaction at Bento Café in Tasikmalaya - Nahdliah, Nida Fitria (Dinasti International Journal of Management Science, 2024)
This study aims to analyze the effect of Service Quality on Perceived Value and Perceived Risk as mediation, and its impact on Customer Satisfaction, with the object of research being the customers of Kafe Bento Tasikmalaya. The research method used is the self-administrated survey method using a questionnaire on a scale of 1-10 and the number of research samples is 235 respondents using purpose sampling. The analysis tool used is Structural Equation Modeling (SEM) with AMOS software. The results show that Service Quality has a positive effect on Perceived Value, but a negative effect on Perceived Risk. Furthermore, Perceived Value has a positive effect on Customer Satisfaction, while Perceived Risk has a negative effect on Customer Satisfaction.